RESEARCH THE DEPOSITION NANO- AND SUBMICRON PARTICLES OF TOBACCO SMOKE ON AIRWAY - V. I. Timoshenko; N. N. Chernov; M. A. Lupandina; O. L. Pyatakova (Бюллетень сибирской медицины)
The features of deposition of highly dispersed particles of smoke on nanoscale biological airway surface on the example of tobacco smoke are considering. A model of particle deposition of the nicotine gum along the way through the smoke inhaled. Obtain a solution of the equation for the diffusion flux changes deposited nano- and submicron particles through hydrodynamic boundary layer.The particle deposition of nicotine gum on the airways by scanning the distribution of nanoparticles deposited using an atomic force microscope SobverPRO was experimentally studied. Patterns of distribution of nanoparticles dispersed smoke 4 species of tobacco in different parts of the respiratory tract were obtained. That allowed to talk about the absence of the effect of coagulation of the airway. It was established that the child as a passive smoker particle deposition diffusive flux of nicotine is proportionally higher than adult because the channel width is less than the airways than in adults.